2016
DOI: 10.3847/0004-637x/818/2/105
|View full text |Cite
|
Sign up to set email alerts
|

THE CALTECH-NRAO STRIPE 82 SURVEY (CNSS) PAPER. I. THE PILOT RADIO TRANSIENT SURVEY IN 50 DEG2

Abstract: We have commenced a multi-year program, the Caltech-NRAO Stripe 82 Survey (CNSS), to search for radio transients with the Jansky VLA in the Sloan Digital Sky Survey Stripe 82 region. The CNSS will deliver five epochs over the entire ∼270 deg 2 of Stripe 82, an eventual deep combined map with a rms noise of ∼40 µJy and catalogs at a frequency of 3 GHz, and having a spatial resolution of 3. This first paper presents the results from an initial pilot survey of a 50 deg 2 region of Stripe 82, involving four epochs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
214
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(225 citation statements)
references
References 133 publications
11
214
0
Order By: Relevance
“…While many of them have not detected any radio transients, Bannister et al (2011) have found 15 in 3000 deg 2 at 10 mJy. Mooley et al (2016) also have found a few radio transients in 50 deg 2 at 0.2 mJy. Two of them are arising from Galactic flaring stars and the others likely from variable AGNs.…”
Section: False Positives: Extragalactic Radio Transients and Variablesmentioning
confidence: 78%
See 3 more Smart Citations
“…While many of them have not detected any radio transients, Bannister et al (2011) have found 15 in 3000 deg 2 at 10 mJy. Mooley et al (2016) also have found a few radio transients in 50 deg 2 at 0.2 mJy. Two of them are arising from Galactic flaring stars and the others likely from variable AGNs.…”
Section: False Positives: Extragalactic Radio Transients and Variablesmentioning
confidence: 78%
“…We estimate the areal densities of radio transients based on the known radio bright astrophysical phenomena(see also Metzger et al 2015b;Mooley et al 2016). Table 5 summarizes relevant values of the radio transients used for the estimates of false positives.…”
Section: False Positives: Extragalactic Radio Transients and Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…While single-field studies are improving our understanding of the sky density of variable sources and its dependence on the flux-limits of these surveys (e.g., Mooley et al 2016), there is only a cursory understanding of the origin of the observed AGN variability in these studies. In the meantime, new surveys have been planned for upcoming radio telescopes, including the Variable and Slow Transients (VAST) Survey (Murphy et al 2013) on the Australia Square Kilometre Array Pathfinder (ASKAP), and eventually the Square Kilometre Array (Bignall et al 2015).…”
mentioning
confidence: 99%